2018
DOI: 10.1161/jaha.118.009946
|View full text |Cite
|
Sign up to set email alerts
|

SUPPORT‐AF: Piloting a Multi‐Faceted, Electronic Medical Record‐Based Intervention to Improve Prescription of Anticoagulation

Abstract: BackgroundOnly 50% of eligible atrial fibrillation (AF) patients receive anticoagulation (AC). Feasibility and effectiveness of electronic medical record (EMR)–based interventions to profile and raise provider AC percentage is poorly understood. The SUPPORT‐AF (Supporting Use of AC Through Provider Profiling of Oral AC Therapy for AF) study aims to improve rates of adherence to AC guidelines by developing and delivering supportive tools based on the EMR to providers treating patients with AF.Methods and Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
3
15
0
1
Order By: Relevance
“…Expert decisional support may have greater traction in the current post-DOAC era as DOACs may be an "easier sell" if GPs are more pre-disposed to using these drugs over warfarin. However, our results are consistent with several randomised and non-randomised evaluations of implementation strategies for reducing stroke risk in AF which mainly report null findings or small differences in the uptake of anticoagulants in the pre and post-DOAC era [32,[36][37][38][39]. Taken together, these findings indicate that shifting prescribing practice remains challenging.…”
Section: Implications For Current Practicesupporting
confidence: 91%
See 1 more Smart Citation
“…Expert decisional support may have greater traction in the current post-DOAC era as DOACs may be an "easier sell" if GPs are more pre-disposed to using these drugs over warfarin. However, our results are consistent with several randomised and non-randomised evaluations of implementation strategies for reducing stroke risk in AF which mainly report null findings or small differences in the uptake of anticoagulants in the pre and post-DOAC era [32,[36][37][38][39]. Taken together, these findings indicate that shifting prescribing practice remains challenging.…”
Section: Implications For Current Practicesupporting
confidence: 91%
“…In contrast, another recent study found no effect of an intervention using email notifications reporting patient-specific stroke risk and guideline recommendations for antithrombotic treatment [36]. Evidence from other randomised and non-randomised trials suggests simply having access to support tools, such as risk calculators, electronically generated feedback reports and automated prompts in anticipation of patient visits does not impact prescribing rates [37][38][39]. Taken together, findings from this and our own research imply that interventions delivered outside the context of the consultation are ineffective, yet providing opportunities for GPs to engage patients in discussions during real-time decision making may drive changes in prescribing behaviour.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Specifically, we worked with an experienced EHR analyst who interrogated the Clarity database associated with Epic Systems EHR to identify demographic information. Through the use of ICD codes that we previously validated, the analyst was also able to identify the presence of comorbid conditions [ 3 , 16 ]. From chart reviews, we also captured the reason why a patient was not on AC.…”
Section: Methodsmentioning
confidence: 99%
“…Оральные антикоагулянты (АК) эффективно снижают риск ишемического инсульта у пациентов с ФП [4], однако недостаточный охват антикоагулянтной терапией (АКТ) [1], назначение субтерапевтических доз АК [2,3] и неудовлетворительная приверженность АКТ [4] могут ослабить профилактический эффект. По разным данным, 25-50% пациентов с ФП, нуждающихся в АК, не получают терапию [5,6]. Чаще всего это связано с пожилым возрастом пациента, высоким риском кровотечения (из-за онкологических заболеваний, высокого риска падений и т.д.…”
Section: ââåäåíèåunclassified